Guide to OCR for Indic Scripts: Document Recognition and Retrieval - Govindaraju, Venu; Setlur, Srirangaraj (Ranga) (Advances in Pattern Recognition, 2009)
This is the first comprehensive text on Optical Character Recognition for Indic scripts. It covers many topics and describes OCR systems for eight different scripts--Bangla, Devanagari, Gurmukhi, Gujarti, Kannada, Malayalam, Tamil and Urdu.